Bureaucracy Involvement In Local Election In Konawe Selatan District - Muh. Najib Husain; Muh. Nasir; Suryani B.B (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
Local Election often makes the bureaucratic apparatus face a dilemma, between being neutral or being involved in politics. Ideally and based on the rules of law, bureaucracy requeired to behave professional and neutral from politics. Despite that in reality it is difficult fot the bureaucratic aparatur to be neutral, moreover when they faced with the temptations and pressures of power. This article highlights the involvement of bureaucracy on local election in Konawe Selatan District, by outlining the modes of bureaucratic involvement, and identifying factors of bureaucratic involvement. This study found that the bureaucrats involved in the Lokal Election were state civil servants and village government officials. Factors that encourage bureaucratic involvement are: the status of incumbent regional head candidates who remain active during the implementation of the elections, the lure of promotion for the bureaucratic apparatus, weak sanctions by the State civil apparatus commission and regional head candidates, and weak supervision and enforcement of election supervisory agencies (Bawaslu and ranks).